Asian approaches to international law and the legacy of colonialism : the law of the sea, territorial disputes, and international dispute settlement - Paek, Chin-hyon.; Yi, Sog-u, 1967-; Tan, Kevin (Abingdon, Oxon : Routledge, 2013)
'Since the conclusion of World War II, the legacy of militarism and colonialism in areas of Asia has left many unresolved conflicts, dividing parts of the region. This legacy has also contributed to the discourse of contemporary legal issues in the region, including territorial disputes, human rights, the environment, state responsibility, and international trade among others. This volume addresses salient international legal issues that flowed from the legacy of the region's historical experience with colonialism. The book specifically addresses topics including territorial boundary disputes, the law of the sea and maritime delimitation, international law and colonialism, responsibility to protect and international dispute resolution. This volume provides perspectives on these issues from prominent Asian legal scholars who analyze and discuss various ways in which international law and the international legal process can aid the resolution of these issues relevant to the region'--
'The chapters in this volume address several salient international legal issues impacted by the legacy of the Asian region's historical experience with colonialism and its current standing in the international system. This volume will provide a perspective on these issues from Asian legal scholars who have embarked on an analysis and discussion of the various ways in which international law and the international legal process can resolve these issues in a manner that is appropriate for the region. The book examines the interconnection between diverse topics, such as current territorial disputes over maritime areas (which includes disputes over maritime delimitation) and the scope of exclusive economic zones in East and Southeast Asia, both of which are aspects of some of the critical political, economic, and legal issues presently confronting the region. These territorial and maritime disputes are partially due to the geography of the region, but the editors make a convincing argument for the genesis of these disputes being rooted in the legacy of the region's colonial past; a legacy which has confounded attempts at resolution of these disputes and still deeply influences international relations in the region. Asian Approaches to International Law and the Legacy of Colonialism will be of particular interest to academics and students of International Law, Maritime Law and Asian Studies'--
Includes bibliographical references and index.
Keywords: Territory, National -- Asia; Territorial waters -- Asia; Boundary disputes -- Asia; International law -- Asia; Economic zones (Law of the sea) -- Asia; Continental shelf -- Law and legislation -- Asia; Colonies (International law) -- Asia -- History; Arbitration (International law)